1992
DOI: 10.1007/bf00174469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of polyethyleneimine on thermal stability and activity of glucose dehydrogenase

Abstract: Abstrzct. When polyethyleneimine (PEI), a water-soluble cationic polymer, was added to solutions of glucose dehydrogenase (GDH) from Bacillus megaterium IWG3 at a molar ratio of PEI to GDH greater than 10, the thermal stability of GDH markedly increased. By addition of PEI, the rate of GDH-catalysed oxidation of flo-glucose increased in a low concentration range of NAD + and NADP + and the Michaelis constants and inhibition constants for both NAD + and NADP + decreased. These results suggested that negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…Polyelectrolyte-enzyme interactions aim at decreasing the denaturation process of a native enzyme, protecting the enzyme from external stresses while at the same time protecting the catalytic activity of the active center. Several investigations have reported that a variety of water-soluble polymers stabilize the enzymatic activities of glucose dehydrogenase, alcohol dehydrogenase, b-galactosidase, and trypsin (32)(33)(34)(35). It has been suggested that electrostatic interactions between the enzymes and the polymers play a dominant role in stabilization of enzyme activities and nonenzymatic proteins (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Polyelectrolyte-enzyme interactions aim at decreasing the denaturation process of a native enzyme, protecting the enzyme from external stresses while at the same time protecting the catalytic activity of the active center. Several investigations have reported that a variety of water-soluble polymers stabilize the enzymatic activities of glucose dehydrogenase, alcohol dehydrogenase, b-galactosidase, and trypsin (32)(33)(34)(35). It has been suggested that electrostatic interactions between the enzymes and the polymers play a dominant role in stabilization of enzyme activities and nonenzymatic proteins (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme immobilization was achieved by a 30 min room temperature incubation of small PR samples with 20 ll solution of LOx in phosphate buffered saline (PBS, pH = 7.4) with 25 wt.% poly(ethyleneimine) (PEI) for stabilization of the enzyme on the PR surface (Teramoto et al 1992;Lin et al 1996). The concentration of LOx in PEI/PBS was varied between 0 mg/ml (no LOx) and 10 mg/ml, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Immobilization of the enzyme on the bare PET surface was achieved by a 30 min room temperature incubation of the sensors with 40 μl 100 U/ml LOx (from Aerococcus viridians, MP Biomedicals, USA) dissolved in PBS with 25 wt.% poly(ethylene)imine for stabilization of the enzyme [24,25].…”
Section: Lactate Sensorsmentioning
confidence: 99%